Dual Gold Catalysis: Synthesis of Fluorene Derivatives from Diynes. Issue 2 (8th December 2016) - Bucher, Janina; Wurm, Thomas; Taschinski, Svenja; Sachs, Eleni; Ascough, David; Rudolph, Matthias; Rominger, Frank; Hashmi, A. Stephen K.
Abstract: 1, 5‐ Diyne systems bearing one terminal and one benzyl‐ or allyl‐substituted alkyne attached to an aromatic backbone were converted in the presence of a gold catalyst. In a dual gold‐catalyzed process, gold vinylidenes are formed that selectively undergo formal CH insertion into the C( sp 2 )–H bond of the offered unsaturated systems. If H atoms are present in the propargylic position, a subsequent isomerization to the aromatic system takes place leading to 9 H ‐fluorene and 11 H ‐benzo[ b ]fluorene derivatives as final products. In the case of a quaternary carbon in the propargylic position no further aromatization is observed and 10 H ‐benzo[ b ]fluorene derivatives are obtained in high yield. Abstract :